PELAJARAN ILMU PENGETAHUAN SOSIAL UNTUK MI YANG MENYENANGKAN - Fifi Nofiturrohmah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
Future learners will face tough challenges due to the global community life is always changing every moment. Therefore, social studies designed to develop knowledge, understanding, and analytical skills of the social conditions in entering a dynamic social life.